Simultaneous laparoscopic treatment of median arcuate ligament syndrome and segmental adenomyomatosis of the gallbladder: A case report. (February 2023) - Kuboki, Daigo; Koide, Ayaki; Taguchi, Satoshi; Yamazaki, Hironobu; Lefor, Alan Kawarai; Tabuchi, Takafumi
Abstract: Introduction: Median Arcuate Ligament Syndrome (MALS) is a condition in which the median arcuate ligament tightly compresses the celiac artery. A patient presented with MALS and segmental adenomyomatosis of the gallbladder, both treated simultaneously using a laparoscopic approach. Presentation of case: A 48-year-old male with adenomyomatosis of the gallbladder presented with postprandial epigastric pain. Abdominal three-dimensional computed tomography scan showed compression of the celiac artery, and the patient was diagnosed with MALS. Laparoscopic dissection of the median arcuate ligament and cholecystectomy were performed to treat both conditions. By optimizing port positions, both conditions could be treated simultaneously. The patient was discharged on postoperative day 6 and has no recurrent symptoms 20 months postoperatively. Discussion: To the best of our knowledge, there are no previously reported cases of simultaneous laparoscopic division of the median arcuate ligament and cholecystectomy. Conclusion: By optimizing the port positions, laparoscopic division of the median arcuate ligament and cholecystectomy were performed simultaneously, minimally invasively, safely and effectively. Highlights: Postprandial epigastric pain due to MALS is often treated as functional dyspepsia. A patient with MALS and adenomyomatosis of the gallbladder was treated simultaneously. An additional port was inserted to dissect the anterior surface of the celiac artery. It is important not to hesitate to add a port to perform the procedure safely. The patient has no recurrent symptoms postoperatively.